The measurements of serum trypsin concentrations in patients With various liver diseases - TERANO, Akira; TAKEDA, Tadanao; KAMISAKA, Kazuaki; MOTOKI, Tatsuya; NAKAMURA, Yuji; KAMII, Kazuo; HIRANO, Masanori; MATSUMOTO, Kazunori; TSURU, Masanobu; SHIBATA, Kyoko; INAGAKI, Tooru; OKANO, Kenichi (Kanzo, 1979)
The serum trypsin concentrations were measured using specific and sensitive radioimmunoassay method. Trypsin levels were (mean±SD); controls 256±57ng/ml; acute hepatitis 383±150; chronic hepatitis 190±71; liver cirrhosis 208±49. There was no corrdation of serum trypsin concentration with alanine transamillase or aspartate transaminase level (r=0.39, r=0.29). Howevcr, serial studies in patients with acute hepatitis, indicated that the dacreases of the tramasvarninase levels were closely associated with the decreases of serum trypsin levels. Though there were no significant difference of the trypsin levels concentrations obtained from renal vein with those from inferior vena cava, serum trypsin Ievels were significantly elevated in patients with chronic renal failure(595±137).